Using climate vulnerability assessments to implement and mainstream adaptation by the forest industry into forest management in Canada - Andrews-Key, Sheri Anne; Nelson, Harry (Frontiers in Forests and Global Change, 2025)
Climate change is an increasing concern for forest managers and society as a whole. The impacts of climate change on forest ecosystems may limit the ability of forest managers to achieve sustainable forest management (SFM) objectives, and changes to management or practices may be required in response. While academic literature emphasizes the need for adaptation to climate change and proposes what kind of higher-level changes are required to facilitate that change, less attention has been paid to what forest managers need and their ability to implement adaptation. In this study, we describe a recent example of proactive climate change adaptation in Canada’s forest industry, the first instance in which a Canadian forest company operating within a publicly owned land base has undertaken a formal climate change adaptation planning process. We show how Mistik Management Ltd., a partnership between nine indigenous nations and a pulp and paper company, used a climate change vulnerability assessment framework to identify vulnerabilities and develop management strategies to mitigate climate risks while also changing management practices. We show how Mistik is mainstreaming climate change considerations into their management system and implementing it through changes in their management practices. At the institutional level, we found no substantive barriers to Canadian forestry firms seeking to incorporate adaptation into ongoing planning and management activities and suggest how the lessons from Mistik’s experiences can inform forest management adaptation policies and processes more generally, not only in Canada but elsewhere.